Analysis of the effectiveness of track lubricators in selected locations in Wrocław - Magdalena Skiba (Przegląd Komunikacyjny)
Abstract: Due to the growing problem of the negative impact of noise, an attempt was made to reduce it by installing track lubricators in several locations in Wroclaw. The article presents the results of measurements in selected tram loops before and after the installation of track lubricators. The collected data were compiled and analyzed together with an indication of the further direction of research.